CareTrack Kids—part 3. Adverse events in children's healthcare in Australia: study protocol for a retrospective medical record review. Issue 4 (8th April 2015) - Hibbert, Peter D; Hallahan, Andrew R; Muething, Stephen E; Lachman, Peter; Hooper, Tamara D; Wiles, Louise K; Jaffe, Adam; White, Les; Wheaton, Gavin R; Runciman, William B; Dalton, Sarah; Williams, Helena M; et al.
Abstract : Introduction: A high-quality health system should deliver care that is free from harm. Few large-scale studies of adverse events have been undertaken in children's healthcare internationally, and none in Australia. The aim of this study is to measure the frequency and types of adverse events encountered in Australian paediatric care in a range of healthcare settings. Methods and analysis: A form of retrospective medical record review, the Institute of Healthcare Improvement's Global Trigger Tool, will be modified to collect data. Records of children aged <16 years managed during 2012 and 2013 will be reviewed. We aim to review 6000–8000 records from a sample of healthcare practices (hospitals, general practices and specialists). Ethics and dissemination: Human Research Ethics Committee approvals have been received from the Sydney Children's Hospital Network, Children's Health Queensland Hospital and Health Service, and the Women's and Children's Hospital Network in South Australia. An application is under review with the Royal Australian College of General Practitioners. The authors will submit the results of the study to relevant journals and undertake national and international oral presentations to researchers, clinicians and policymakers.